Ternary surface complexation promotes simultaneous removal of arsenic and uranium by TiO 2 - Leiming Lin; Zheng Li; Jun Ren; Ying Meng; Fubo Luan (Proceedings of the National Academy of Sciences, 2025)
The co-occurrence of arsenic and uranium in groundwater has been found in many countries, posing a significant challenge to human health. Here, we have demonstrated the efficient simultaneous removal of arsenic and uranyl-carbonate complexes from groundwater using {001}-TiO 2 . Surprisingly, the presence of U(VI) greatly enhanced the adsorption of As(V) on {001}-TiO 2 , while As(V) had a negligible impact on U(VI) adsorption. Through in situ ATR-FTIR spectroscopy, we uncovered a mechanism involving the formation of a ternary surface complex [Ti–U(VI)–As(V)] on the surface of {001}-TiO 2 . This ternary surface complex formed through the substitution of CO 3 2- from uranyl coordination sites. Furthermore, the adsorbed As(V) and U(VI) can be easily recovered using a sodium hydroxide solution, and {001}-TiO 2 can be used repeatedly. Our findings offer a promising solution for the simultaneous removal of As(V) and U(VI) from groundwater and provide valuable insights into the mechanisms involved in their removal.